Enhanced performance of photocatalytic CO2 reduction via synergistic effect between chitosan and Cu:TiO2. (April 2020) - She, Houde; Zhao, Ziwei; Bai, Wencai; Huang, Jingwei; Wang, Lei; Wang, Qizhao
Graphical abstract: The Cu:TiO2 -CS composite was synthesized by a facile solvothermal process, which exhibits excellent photocatalytic CO2 reduction performance. Highlights: The Cu:TiO2 -CS composite was successfully synthesized by a solvothermal treatment method. Cu:TiO2 -CS sample exhibited excellent photocatalytic CO2 reduction capability than TiO2, TiO2 -CS and Cu:TiO2 sample. The synergistic effect between chitosan and Cu:TiO2 in Cu:TiO2 -CS composite facilitated the performance of CO2 reduction improvements. Abstract: Photocatalytic CO2 reduction is considered as a feasible approach for solving greenhouse effect and energy shortage. Promoting electron migration and inhibiting electron-hole recombination are key challenges for efficient photocatalytic CO2 reduction. Here, we successfully synthesized Cu:TiO2 -CS composite as photocatalyst by a facile solvothermal method to improve the high-catalytic effect on CO2 reduction. The as-prepared composite exhibits excellent photocatalytic CO2 reduction performance under 300 W xenon lamp irradiation, with the yields of CO and CH4 up to 4.48 μmol/g and 5.34 μmol/g, which is 10 times higher than that of TiO2 . This impressive amelioration can be attributed to the synergy of organic polymer (chitosan) and inorganic material (Cu:TiO2 ). This work may provide a constructing guidance in designing the composite photocatalyst concerning CO2 photocatalytic reduction.